2006
DOI: 10.1152/ajpheart.00692.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of superoxide and angiotensin II suppression in salt-induced changes in endothelial Ca2+ signaling and NO production in rat aorta

Abstract: Male Sprague-Dawley rats were maintained on a low-salt (LS) diet (0.4% NaCl) or changed to a high-salt (HS) diet (4% NaCl) for 3 days. Increases in intracellular Ca 2ϩ ([Ca 2ϩ ]i) in response to methacholine (10 M) and histamine (10 M) were significantly attenuated in aortic endothelial cells from rats fed a HS diet, whereas thapsigargin (10 M)-induced increases in [Ca 2ϩ ]i were unaffected. Methacholineinduced nitric oxide (NO) production was eliminated in endothelial cells of aortas from rats fed a HS di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 35 publications
8
91
0
Order By: Relevance
“…Increased O 2 .Ϫ could reduce the bioavailability of NO, resulting in impairment of endothelium-dependent vasodilation, as shown in our previous studies and by others. 4,[41][42][43][44] In summary, the present study demonstrated that EST is able to induce endothelial dysfunction as an early-stage acute action, which is associated with assembling and activation of NADPH oxidase in LR clusters. The clustered LRs together with activated NADPH oxidase constitute a redox signaling platform mediating the pathological actions of EST on the vascular endothelium.…”
Section: Discussionsupporting
confidence: 55%
“…Increased O 2 .Ϫ could reduce the bioavailability of NO, resulting in impairment of endothelium-dependent vasodilation, as shown in our previous studies and by others. 4,[41][42][43][44] In summary, the present study demonstrated that EST is able to induce endothelial dysfunction as an early-stage acute action, which is associated with assembling and activation of NADPH oxidase in LR clusters. The clustered LRs together with activated NADPH oxidase constitute a redox signaling platform mediating the pathological actions of EST on the vascular endothelium.…”
Section: Discussionsupporting
confidence: 55%
“…The increased influx of Ca 2+ in mutant vessels coincided with elevated NO bioavailability ( Fig. 6 A and B), fitting with previous reports of Ca 2+ -mediated regulation of NO bioavailability in the endothelium (28,29,44,45). Because endothelial NO synthase (eNOS) activity is highly dependent on Ca 2+ and inhibition of eNOS with L-NAME blocked FMD and ACh-mediated NO release in the mutant rats, we propose that Plekha7 is signaling through this pathway; however, additional studies will be needed to determine the connection between Plekha7 and eNOS.…”
Section: Plekha7 Modulates Vasodilator Responses Via Endothelial Calciumsupporting
confidence: 91%
“…Flow studies were carried out as described previously (52). NO levels were measured in aortas using DAF-FM diacetate and imaging the fluorescent response to the addition of 2 mM ACh, as described previously (45). Ca 2+ transient studies were performed on aortas loaded with Fluo-4.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, vasodilator responses to ACh and reduced PO 2 that were absent in sham-operated controls fed an HS diet were restored by infusion of ANG II at a dose previously shown to prevent salt-induced ANG II suppression. 16,17,30 Because administration of losartan before the diet change eliminated vascular relaxation in 2K1C rats fed an HS diet, the maintenance of vasodilator responses to ACh and reduced PO 2 in HS-fed 2K1C rats is most likely related to the persisting effects of AT 1 receptor activation to upregulate antioxidant defenses (e.g., Cu/Zn SOD) (Figure 2) in response to the elevated ANG II levels after unilateral renal artery clipping. Those findings provide additional support for the hypothesis that tonic interaction of ANG II with the AT 1 receptor plays an important role in maintaining normal vascular relaxation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous intravenous infusion of a low dose of ANG II to prevent the salt-induced decrease in plasma ANG II levels not only restores ACh-induced dilation that is lost in cerebral arteries of HS-fed Sprague-Dawley rats [9][10][11]19 but also reduces vascular superoxide levels to NS values and maintains nitric oxide availability in small mesenteric arteries 12 and aortas 30 of HS-fed Sprague-Dawley rats. Low-dose ANG II infusion also prevents the downregulation of Cu/Zn SOD in cerebral arteries of Sprague-Dawley rats fed an HS diet.…”
Section: Discussionmentioning
confidence: 99%